2008
DOI: 10.23941/ejpe.v1i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Is history of economic thought a "serious" subject?

Abstract: The purpose of this paper is to clarify the nature of research methods in the history of economic thought. In reviewing the "techniques" which are involved in the discipline, four broader categories are identified: a) textual exegesis; b) "rational reconstructions"; c) "contextual analysis"; and d) "historical narrative". After examining these different styles of doing history of economic thought, the paper addresses the question of its appraisal, namely what is good history of economic thought. Moreover, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…Different research styles and methods in the history of economic thought are presented and discussed e.g. in Samuels (1983), Medema and Samuels (2001), Biddle (2003), Samuels et al (2003), Marcuzzo (2008) and Sandmo (2011). Marcuzzo (2008) identifies four broad methods in the history of economic thought: i) textual exegesis; ii) rational reconstructions; iii) contextual analysis; and iv) historical narrative.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different research styles and methods in the history of economic thought are presented and discussed e.g. in Samuels (1983), Medema and Samuels (2001), Biddle (2003), Samuels et al (2003), Marcuzzo (2008) and Sandmo (2011). Marcuzzo (2008) identifies four broad methods in the history of economic thought: i) textual exegesis; ii) rational reconstructions; iii) contextual analysis; and iv) historical narrative.…”
Section: Methodsmentioning
confidence: 99%
“…It accords its practitioners the right to establish the demarcation criterion for deciding the scientific character of given texts and consists of reviewing them in the light of the interpreter's contemporary economic knowledge. A coherent application of the method requires that the practitioner is first able to reconstruct the "general position" of the theoretical core of an author's work in a manner compatible with contemporary economic theory (Stigler 1965;Emmett 2003, 525;Marcuzzo 2008). However, a major problem in this notion lies in the implicit assumption that the interpreter already knows the author's general position before he or she begins to interpret the text.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Una investigación de este tipo reclama una "historia razonada" de los sistemas de pensamiento; lo cual significa encontrar esquemas heurísticos que faciliten el itinerario de reconstrucción historiográfica de las ideas económicas. Al respecto, Marcuzzo (2008) ha identificado cuatro métodos relevantes para una investigación orientada a la historia del pensamiento económico: a) exégesis textual; b) reconstrucción racional; c) análisis contextual; y d) narrativo histórico.…”
Section: Métodos Para La Labor Historiográficaunclassified
“…Relevant pages of literature and history of economic thought such as (Jhingan, 2007;Marcuzzo, 2008;Bhatia, 2004;Akpakpan, 1999;Tamuno, 2006;Okowa, 1996;Kalu, 2001;Blang, 2001;Todaro and Smith, 2004; and Samuelson and Salow 1960) have consistently revealed that the adoption and complete application of the doctrines, ideas, model, philosophy; in fact all the contributions of economists of old (chronology of the founding fathers) have led to the emergence of the discipline and without doubts equally accorded for the reason why some economies are said to be developed and others are said to be underdeveloped. Obviously, the Nigeria economy is categorized in the latter.…”
Section: Introductionmentioning
confidence: 99%